2015
DOI: 10.1038/srep09475
|View full text |Cite
|
Sign up to set email alerts
|

Opposite rheological properties of neuronal microcompartments predict axonal vulnerability in brain injury

Abstract: Although pathological changes in axonal morphology have emerged as important features of traumatic brain injury (TBI), the mechanical vulnerability of the axonal microcompartment relative to the cell body is not well understood. We hypothesized that soma and neurite microcompartments exhibit distinct mechanical behaviors, rendering axons more sensitive to a mechanical injury. In order to test this assumption, we combined protein micropatterns with magnetic tweezer rheology to probe the viscoelastic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 66 publications
(74 reference statements)
8
62
0
Order By: Relevance
“…However, a more recent study using magnetic tweezers for local rheological measurements revealed that the soma is softer and more solid-like compared with the stiff and viscous-like neurites. The authors concluded that axons are probably more sensitive to mechanical damage than the soma 28 . However, the main load-bearing direction of neural processes is actually oriented along their length, in which elastic spring constants of a few hundred mN m −1 , viscoelastic relaxation and also active contraction have been observed [29][30][31][32][33][34] .…”
Section: Cellular Considerationsmentioning
confidence: 99%
“…However, a more recent study using magnetic tweezers for local rheological measurements revealed that the soma is softer and more solid-like compared with the stiff and viscous-like neurites. The authors concluded that axons are probably more sensitive to mechanical damage than the soma 28 . However, the main load-bearing direction of neural processes is actually oriented along their length, in which elastic spring constants of a few hundred mN m −1 , viscoelastic relaxation and also active contraction have been observed [29][30][31][32][33][34] .…”
Section: Cellular Considerationsmentioning
confidence: 99%
“…6,23 Briefly, magnetic beads were coated with fibronectin and incubated with patterned cells in order to bind the magnetic beads to the cytoskeleton through formation of focal adhesions. 6 A constant magnetic pulling force was applied to the beads during 12 s and the elastic modulus of living micropatterned cells was estimated with Eq. 6 by using bead displacements that were recorded with time-lapse microscopy.…”
Section: Cellular Relaxation Dynamics Is Modulated By Matrix Stiffnessmentioning
confidence: 99%
“…A home-made magnetic tweezer mounted on an inverted Nikon Eclipse Ti microscope (Nikon, Japan) and connected to a LabVIEW software (National Instruments, Austin, Texas) was positioned at a 35-degree angle to the microprinted culture substrate by using an automated micromanipulator system (InjectMan NI2, Eppendorf, Hamburg, Germany). 6 The magnetic forces were calibrated using the Stokes' law by quantifying the beads displacements in a 99% glycerol solution as a function of the current intensity and the bead-tip distance. A constant pulling force, F, was then applied to paramagnetic beads of section S and radius R bounded to the cytoskeleton of the micropatterned endothelial cells.…”
Section: Measurement Of Cell Stiffness By Magnetic Tweezersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the question of the mechanical vulnerability of the axon over the soma remained misunderstood. We addressed this issue by combining microcontact printing and magnetic tweezers to apply local stresses on paramagnetic beads bound to individual microcompartments of bipolar cortical neurons and measured the creep response [29] . Our results indicate that the axon is characterized by a pronounced viscous state, while the soma behaves like an elastic solid (Fig.…”
Section: Research Highlightmentioning
confidence: 99%